2014
DOI: 10.3349/ymj.2014.55.5.1373
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated with Amputation-Free Survival in Patient with Diabetic Foot Ulcers

Abstract: PurposeTo determine the 1-year survival rate, 1-year amputation-free survival rate and the risk factors of amputation for patients with diabetic foot ulcers.Materials and MethodsOne hundred seventy-three patients with diabetic foot ulcers were included in our study. Mean patient age was 67.5 (range, 29 to 87, SD ±11.4) years. 74% of the patients were male. Time from study entry to amputation and time to death were evaluated separately as censored event times by Kaplan-Meier curves and log-rank tests. A multiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
42
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 16 publications
4
42
1
1
Order By: Relevance
“…Several risk factors have been associated with increased risk of amputation in patients with diabetes such as neuropathy, ulcer severity (hazard ratio (HR): 7.99; confidence interval (CI): 3.12 to 20.47), peripheral artery disease (HR: 2.64; CI: 1.52 to 4.59) [ 11 ], infection and diabetes control (measured as Hb1ac%) [ 12 , 13 ]. Also the role of chronicity in DFU is not well explored but might be associated with increased incidence of amputations in diabetic patients and it has been described that ulcer size and depth is a risk factor for amputation [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several risk factors have been associated with increased risk of amputation in patients with diabetes such as neuropathy, ulcer severity (hazard ratio (HR): 7.99; confidence interval (CI): 3.12 to 20.47), peripheral artery disease (HR: 2.64; CI: 1.52 to 4.59) [ 11 ], infection and diabetes control (measured as Hb1ac%) [ 12 , 13 ]. Also the role of chronicity in DFU is not well explored but might be associated with increased incidence of amputations in diabetic patients and it has been described that ulcer size and depth is a risk factor for amputation [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the stepwise multivariate analysis, dialysis maintained statistical significance (OR = 8·683, P < 0·001). Previous studies have shown that chronic kidney disease (CKD) and current dialysis for end‐stage renal disease (ESRD) were independent risk factors for diabetic foot ulceration and major amputation. Young et al reported that the relative risk of amputation among the diabetic patients was the highest among those who started dialysis.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, Winkley et al showed that a lower HbA1c level was associated with higher mortality. Won et al showed that patients with a mean HbA1c level below 7·5% had a 52% higher risk of amputation compared with patients with a mean HbA1c level above 7·5%. In our study, HbA1c was not found to be a predictive factor.…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that approximately 15–25% of diabetic patients develop diabetic foot ulcers during the course of the disease. People with diabetes can progress into chronic ulcers often leading to amputation if not treated promptly [ 4 6 ]. Age, male gender, and long duration of diabetes are the other factors associated with amputation [ 4 , 7 ].…”
Section: Introductionmentioning
confidence: 99%